Design of adaptive optics by interference fitting: Theoretical background. (March 2022) - Esposito, L.; Bertocco, A.; Bruno, M.; Ruggiero, A.
Highlights: An analytical solution to predict the curvature and deflection of a thermally actuated deformable mirror with compression bias was presented. The effect of the material properties and different assembling conditions on the final deformed configuration were taken into account. The proposed formulation was compared to numerical analysis and experimental evidences, showing a good correlation with respect to all the considered deformation and stresses parameters. The analytic formulation opens up the possibility of multiobjective optimization of these adaptive optical systems. Abstract: Interference-fit joints are typically adopted to produce permanent assemblies among mechanical parts. The resulting contact pressure is generally used for element fixing or to allow load transmission. Nevertheless, some special designs take advantage of the contact pressure to induce desiderata deformation or to mitigate the stress field inside the structure. Biased interference fitting between a planar mirror and an external ring could be used to induce the required curvature to realize new adaptive lens for optical aberration correction. Recently, thermally-actuated deformable mirror on this principle based, was proposed and prototyped. Although the feasibility and utility of such innovative lens was demonstrated, no comprehensive theory was developed to describe mirror behavior and predict their curvature. Nowadays, the use of approximated numerical approach, such as the finite element method, is the only way to study the interaction between biased and interference fitted bodies. The paper aims to give the theoretical background for the correct design of adaptive lens actuated by interference fitting. A new formulation for the curvature prediction is proposed and compared with finite element analysis and available experimental measurements. Graphical abstract: Image, graphical abstract